2011
DOI: 10.1007/s11095-011-0426-5
|View full text |Cite
|
Sign up to set email alerts
|

How Stealthy are PEG-PLA Nanoparticles? An NIR In Vivo Study Combined with Detailed Size Measurements

Abstract: We combined narrow-size distributed nanoparticle batches with detailed in vitro characterization and the understanding of their in vivo fate using fluorescence imaging, confirming the wide possibilities of the non-invasive technique and presenting the basis to evaluate future size-dependent passive tumor accumulation studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 49 publications
(61 reference statements)
7
56
0
Order By: Relevance
“…FRET-NPs were found to be stable in deionized water, with no significant changes in both the size and zeta potential for 7 days ( Figure 6A). 53 In addition, there was no observable change in the size of FRET-NPs that were stored in PBS only or 10% (v/v) of FBS in MEM media ( Figure 6B). However, in the presence of 4.5% (w/v) of BSA, the particles were slightly increased in size after 24 h. This could be due to the adsorption of proteins on the particle surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…FRET-NPs were found to be stable in deionized water, with no significant changes in both the size and zeta potential for 7 days ( Figure 6A). 53 In addition, there was no observable change in the size of FRET-NPs that were stored in PBS only or 10% (v/v) of FBS in MEM media ( Figure 6B). However, in the presence of 4.5% (w/v) of BSA, the particles were slightly increased in size after 24 h. This could be due to the adsorption of proteins on the particle surfaces.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…SSL-DiR and iRGD-SSL-DiR exhibited similar size distribution (134.9 ± 9.66 nm and 131.6 ± 11.6 nm, respectively) and zeta potential (À2.46 ± 0.85 mV and À3.19 ± 0.30 mV, respectively). As shown in Figure 5A, though liposomal formulations significantly improved circulation profiles and had EPR effect owing to PEG modification (Minko et al, 2006), there was high accumulation in liver and spleen as shown in the ex vivo image ( Figure 5B), possibly because of the arrestment of DiR-loaded formulations by RES system (Schädlich et al, 2011;Xiang et al, 2011). However, superior distribution of liposomes, especially iRGD-SSL-DiR at 12-h post-injection, in tumors could still be observed.…”
Section: Cytotoxicity Assaymentioning
confidence: 96%
“…Although the high accumulation in liver and spleen was observed in the ex vivo images (Fig. 7B), which was possibly caused by the arrestment of DiR formulations by RES [36,37], more tumoral accumulation of SSL-DiR in the combinational regimen could also be noticed. Nanomedicines with a size around 100 nm, such as liposomes, could be effectively transported to tumors by EPR effect; however, they were found to distribute in a limited perivascular region and could not penetrate into tumor tissue further [38].…”
Section: Enhanced Liposomal Delivery Into Tumor By Decreasing Tumor Ifpmentioning
confidence: 96%